2015
DOI: 10.1039/c5sm01560j
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-mediated nanorod self-assembly predicted by dissipative particle dynamics simulations

Abstract: Self-assembly of nanoparticles in polymer matrices is an interesting and growing subject in the field of nanoscience and technology. We report herein on modelling studies of the self-assembly and phase behavior of nanorods in a homopolymer matrix, with the specific goal of evaluating the role of deterministic entropic and enthalpic factors that control the aggregation/dispersion in such systems. Grafting polymer brushes from the nanorods is one approach to control/impact their self-assembly capabilities within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 41 publications
4
45
0
Order By: Relevance
“…It is reported that by employing the integral equation theory, NRs exhibit the contact aggregation, dispersion, bridging, and tele-bridging behavior with tuning the polymer-NR interaction. 45 In our systems, NRs mainly form the contact aggregation and bridging structures at λ A ≤ 0.2, while NRs mainly form the bridging and tele-bridging structures at λ A ≥ 0.4. To intuitively observe the NR dispersion state, the snapshots are shown in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…It is reported that by employing the integral equation theory, NRs exhibit the contact aggregation, dispersion, bridging, and tele-bridging behavior with tuning the polymer-NR interaction. 45 In our systems, NRs mainly form the contact aggregation and bridging structures at λ A ≤ 0.2, while NRs mainly form the bridging and tele-bridging structures at λ A ≥ 0.4. To intuitively observe the NR dispersion state, the snapshots are shown in Fig.…”
Section: Resultsmentioning
confidence: 62%
“…Here, K b = 100, r 0 = 0.6 r C is used for gelatin 49 and K b = 20, r 0 = 0.85 r C is used for PVDF. 42 The harmonic angle style potential U θ = K θ (θ – θ 0 ) 2 is applied on two consecutive bonds for both gelatin and polymer chains, where K θ , θ, and θ 0 are the bending constant, inclination angle, and equilibrium angle. For three consecutive skeleton beads (S) of gelatin or three consecutive PVDF beads (P), the bending constant and equilibrium angle are set as K θ = 6 and θ 0 = 180° to keep the chain structures.…”
Section: Methodsmentioning
confidence: 99%
“…(II) The nanoparticle is equivalent to a large-volume bead, and other small beads can be modified on the surface of these large beads with bead bonds to change the solvophilicity of those nanoparticles. By virtue of those modeling methods, researchers have completed a series of studies on the self-assembly of liquid crystal polymers (polymer with rigid molecular side chains), and then nanorods, , nanotubes, ,, and other nanoparticles were successfully modeled and introduced into the DPD simulation.…”
Section: Application Scope Of Dpd Simulationmentioning
confidence: 99%